An Automatic Miniature Surface Plasmon Resonance System for Cortisol Detection. (2017) - Zhang, Lulu; Chen, Xing; Wei, Wei; Deng, Shaoli; Xu, Chunfang; Cui, Dafu
Abstract: This paper presents a homemade miniature surface plasmon resonance (SPR) system with automatic sample injection device which is able to work 24 hours unattended. The system with a volume of 48cm×25cm×28 cm was constructed with a red laser light source, a P-polarizer, a triangle glass prism, a linear CCD detector, gold sensor chips modified with BSA or colloidal gold, an automatic sample injection device with 20 sample locations. The system sensitivity and noise were tested through detecting different concentration of glycerol solutions with a group of refractive indices (RIs). Cortisol-BSA was fixed on the gold sensor chips modified with BSA or colloidal gold. A series concentration of cortisol (1, 10, 100, 1000 ng/ml) mixed with cortisol-specific monoclonal antibodies were detected by miniature SPR system. The performance of BSA and colloidal gold modified sensor chips were compared by calculating the standard curves and the kinetic curves of the cortisol detection. The results showed that the BSA sensor chip could get a better detection limit of cortisol sample while the colloidal gold sensor chip owed a higher stability and repeatability by regenerating the antibody surface. The research studied the performance of the homemade SPR system and the sensor chips which could be widely used in the protein measurement areas.